1996
DOI: 10.1111/j.1348-0421.1996.tb01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Characterization of Trichosporon cutaneum and Related Species

Abstract: Recent molecular biological, chemical, physiological and morphological studies indicate that Tri-chosporon cutaneum and related species should be reclassified. In this study, antigenic characteristics of the species were determined. The results of adsorption experiments revealed that there were at least three serological types: I, II and III. Specific factor sera I, II and III were prepared on the basis of adsorption experiments and isolates were serotyped by cell slide agglutination (CSA). Since the CSA test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
0
24
1
Order By: Relevance
“…Strains CBS 1896, 1987 and 2043 were serotyped with specific factor sera for Trichosporon as described by Ikeda et al (6).…”
Section: Methodsmentioning
confidence: 99%
“…Strains CBS 1896, 1987 and 2043 were serotyped with specific factor sera for Trichosporon as described by Ikeda et al (6).…”
Section: Methodsmentioning
confidence: 99%
“…Since 1984, when Shimazu et al (15) first reported that SHP was induced by Trichosporon, the number of patients reported to suffer from SHP has been increasing steadily. When the role of Trichosporon in SHP was first ascertained, T. cutaneum was considered to be the causative antigen, and four serotypes were identified, namely I, II, III, and I-III (9,12). Patients with SHP had positive reactions to inhalation challenge with antigens of the same serotype of T. cutaneum isolated from their houses, indicating that patients are sensitized by exposure to the dominant Trichosporon species in their home environment (3).…”
mentioning
confidence: 99%
“…Serotype was determined by a slide agglutination test using specific-factor sera as described by Ikeda et al (6).…”
Section: Methodsmentioning
confidence: 99%
“…Since 1984, when SHP caused by Trichosporon species was first reported by Shimazu et al (12), the number of patients reported to suffer from this disease has been increasing steadily. Serologically, at least four different types (I, II, III and I-III) have been identified in the Trichosporon species (6,10). Most of the environmental strains isolated from SHP patients' houses are serotype I or II.…”
mentioning
confidence: 99%